The History of the Formation and Development of the Higher Education System in the Republic of Kazakhstan: Main Problems and Prospects - Berdaliyev, D.T.; Aldabergenova, M.K.; Masalieva, Zh.A. (Karagandy University of the name of acad. E.A. Buketov, 2025)
Globalization processes at the present stage have a significant impact not only on the development of the material, technical, scientific, and theoretical foundations of social progress, but also on socio-political and ideological processes and the formation of progressive social consciousness. Over the past decade, Kazakhstan has seen significant changes in the organization of education management, the formation of a regulatory and legal framework, the overcoming of a departmental approach to the management of educational institutions, and the growing role of associations of educational institutions. Kazakh society has developed a new approach to understanding modern education, based on its quality and the introduction of the latest innovative technologies. In this regard, research into the management of the higher education system requires consideration of the experience of educational reforms and, above all, an understanding of the historical experience of its development. The article identifies the problems of managing the Kazakhstani higher education system in the process of reform at various stages of its development. The authors of this article justify the need to develop the management of Kazakhstan’s higher education system at the present stage, examine problematic issues, and explore promising areas for the development of Kazakhstan’s higher education system. An analysis of the history of development and reform processes in the higher education system of the Republic of Kazakhstan has allowed the authors to identify the main positive characteristics that meet international requirements. The article examines the changes taking place in the higher education system under the influence of globalization processes and identifies its main characteristics at the present stage.
Keywords: education policy; reforms; education management; globalization; Kazakh higher education system; education system; history of higher education system; Republic of Kazakhstan